Land‐Atmosphere Interactions Exacerbated the Drought and Heatwave Over Northern Europe During Summer 2018. Issue 2 (15th April 2021) - Dirmeyer, Paul A.; Balsamo, Gianpaolo; Blyth, Eleanor M.; Morrison, Ross; Cooper, Hollie M.
Abstract: The 2018 drought and heatwave over northern Europe were exceptional, with unprecedented forest fires in Sweden, searing heat in Germany and water restrictions in England. Monthly, daily, and hourly data from ERA5, verified with in situ soil water content and surface flux measurements, are examined to investigate the subseasonal‐to‐seasonal progression of the event and the diurnal evolution of tropospheric profiles over Britain to quantify the anomalous land surface contribution to heat and drought. Data suggest the region entered an unprecedented condition of becoming a "hot spot" for land‐atmosphere coupling, which exacerbated the heatwave across much of northern Europe. Land‐atmosphere feedbacks were prompted by unusually low soil water over wide areas, which generated moisture limitations on surface latent heat fluxes, suppressing cloud formation, increasing surface net radiation, and driving temperatures higher during several multiweek episodes of extreme heat. We find consistent evidence in field data and reanalysis of a threshold of soil water content at most locations, below which surface fluxes and daily maximum temperatures become hypersensitive to declining soil water. Similar recent heatwaves over various parts of Europe in 2003, 2010, and 2019, combined with dire climate change projections, suggest such events could be on the increase. Land‐atmosphere feedbacks may play an increasingly important role in exacerbating extremes, but could also contribute to their predictability on subseasonal time scales. Plain Language Summary: This study uses a combination of environmental observations, atmospheric, and land surface analyses over northern Europe to examine the exceptional drought and heatwave during the summer of 2018. Results suggest the region entered a state of positive feedback between the land and atmosphere, exacerbating the heatwave over the area. This is a situation that is common over southern Europe and many other places in the world, but not for northern Europe. Dry soils and vegetation led to reduced evaporation, increased heating of the surface, warming and drying of the air, contributing to less cloud cover and rain. Particularly, a threshold value of soil water content has been found for most locations, below which evaporation, heating, and daily maximum temperatures become significantly more sensitive to declining soil water. This is both a worrying indicator for the region in a warming climate and a potential source of additional predictability for the intensification of future heatwave events. Key Points: Unprecedented dry soil contributed to the 2018 European heatwave and drought by altering surface fluxes, heating, and drying the atmosphere Threshold values of soil water content are found below which air temperature becomes much more sensitive to increased drying Field observations corroborate reanalysis depictions of heatwave sensitivity, suggesting land feedbacks amplified heat over much of Europe